Algae toxicological assessment and valorization of energetic-laden wastewater streams using Scenedesmus obliquus. (20th November 2018) - Abraham, Juliana; Lin, Yanxia; RoyChowdhury, Abhishek; Christodoulatos, Christos; Conway, Matthew; Smolinski, Benjamin; Braida, Washington
Abstract: The manufacturing of energetic compounds (explosives), such as 1, 3, 5-trinitroperhydro-1, 3, 5-triazine (RDX) and 3-nitro-1, 2, 4-triasol-5-one (NTO), generates large volumes of wastewater containing organic pollutants, which are also rich in nutrients, mainly nitrogen. These wastewaters are subject to regulatory compliance and require treatment prior to their release into local water bodies. An approach is proposed to recover nutrients and water from wastewaters prior to treatment by growing microalgae with the aim to reduce the energy footprint of the munitions production facility by producing algae-based biofuels. In order to assess the feasibility of implementation of the proposed approach, ten different fully characterized untreated wastewaters with various levels of organic and inorganic carbon and nitrogen content were assessed for microalgae toxicity using Scenedesmus obliquus ATCC ® 11477 as target microorganism. Toxicity experiments were performed in microplates for six days at 25 °C, 120 rpm orbital mixing speed, under a 14:10 h light: dark photoperiod, and 68 μmol photons/m 2 s of light intensity. The results indicate that the majority of the wastewater streams assessed could be used as nutrient media with no pretreatment while only three of the streams required chemical treatment due to their high growth inhibition characteristics. From the toxicological results obtained, a site specific mixture prepared by blending of the different untreated waste streams was tested for Scenedesmus obliquus growth. It was observed that this microalga can reach 5 × 10 7  cells/mL over six days of incubation in the wastewater mixture containing up to 24 mg/L RDX and 28 mg/L NTO. This strain exhibited similar growth patterns in the wastewater mixture as compared to the control sample, suggesting the potential feasibility of using untreated, energetic-laden industrial wastewater along with carbon dioxide [CO2 (atmospheric or flue gases)] for microalgae biomass production. Graphical abstract: Image 1 Highlights: Algae toxicity assessments of wastewaters from a munition production facility. The majority of untreated wastewaters analyzed were not toxic to Scenedesmus obliquus. A blend of untreated wastewaters was formulated to recover nutrients for algae growth. A proof of concept for valorizing wastewaters from a munition production facility.